Context dependence of female reproductive competition in wild chacma baboons. (May 2018) - Baniel, Alice; Cowlishaw, Guy; Huchard, Elise
Abstract : Recent research reveals that female reproductive competition is common and may shape the social and reproductive strategies of female mammals. This study explores the determinants and intensity of female intrasexual conflicts in a wild promiscuous primate, the chacma baboon, Papio ursinus . We tested a suite of hypotheses to assess whether female–female aggression was primarily driven by instantaneous competition for food, mates or paternal care, or aimed at reducing future competition among offspring via reproductive suppression. Behavioural data were gathered from 53 females in two groups over two contrasting 2-year periods (2005–2006, 2013–2014): the first characterized by stability in the male dominance hierarchies, the second by instability induced by several immigration events and male take-overs. In both periods, we found that sexually receptive females received high levels of aggression from other sexually receptive females, consistent with competition over mating opportunities. In the unstable period, females exchanged higher rates of aggression than in the stable period, regardless of reproductive state, but lactating females received most aggression, consistent with higher competition over social access to male partners in response to increased infanticide risk. There was no evidence that aggression between females reflected either competition over food or reproductive suppression. These findings indicate that patterns of aggression between females fluctuate with sociodemographic factors affecting sexual and social access to males and reflect reproductive competition more closely than resource competition in this promiscuous primate society. Highlights: Female–female aggression preferentially targets fertile females in chacma baboons. This suggests that females compete over access to mates in this promiscuous society. Lactating females also compete over paternal services, when infanticide risk is high. The intensity and determinants of female intrasexual conflicts are context dependent.